Code of Ethics - de la Cruz Lázaro, Efraín (Ecosistemas y Recursos Agropecuarios, 2018)
The journal Ecosistemas y Recursos Agropecuarios is committed to complying with and respecting the princi- ples of transparency and good practices set out in the academic publications of the Committee on Publication Ethics (COPE). The present code of ethics refers to the honesty of the Authors, the Editorial Committee and the Reviewers. In this context, the journal Ecosistemas y Recursos Agropecuarios demands: a) from authors, originality and authenticity in their manuscripts; b) from editors and reviewers, transparency and objectivity in the review process; and c) from all those involved, not to engage in scienti c fraud.